P‐179: Color Tunable Thermally Activated Delayed Fluorescence Emitters with Changing Electron Withdrawing Characteristic of Acceptor. Issue 1 (30th May 2018) - Ko, A Ra; Lee, Dong Ha; Ji, Seung Bae; Choi, Hye Won; Yook, Kyoung Soo
Abstract : A series of thermally activated delayed fluorescence (TADF) emitters of 2, 2′, 2″‐(1, 3, 5‐triazine‐2, 4, 6‐triyl)tris(N, N‐diphenylaniline) (TPA‐Trz), 2, 2′, 2″‐(pyrimidine‐2, 4, 6‐triyl)tris(N, N‐diphenylaniline) (TPA‐Pyr), 2, 2′, 2″‐(pyridine‐2, 4, 6‐triyl)tris(N, N‐diphenylaniline) (TPA‐Py) are synthesized. Photophysical and electrical properties of TADF emitters were characterized according to the electron withdrawing strength of the molecule, by integrating triphenylamine electron donating unit and triazine, pyrimidine, pyridine electron withdrawing unit. Energy bandgap between the highest occupied molecular orbital (HOMO) and the lowest occupied molecular orbital (LUMO) was controlled by changing the electron withdrawing strength of electron accepting unit of the molecule. Triazine based molecule TPA‐Trz (0.12 eV) showed smallest ΔEST value than TPA‐Pyr (0.25 eV) and TPA‐Py (0.27 eV), and the maximum photoluminescence emission peak of TPA‐Trz, TPA‐Pyr, and TPA‐Py was 516, 470 and 441nm, respectively. TPA‐Trz device showed maximum external quantum efficiency of 19.7% with a CIE color coordinate of (0.30, 0.61) and TPA‐Pyr showed maximum external quantum efficiency of 13.9% with a CIE color coordinate of (0.16, 0.30).